Finland : School Autonomy and Accountability - World Bank (Washington, DC, 2014)
The two most important factors explaining the success of the Finnish education system are: education has been a national priority for decades, and the system operates on trust. The Ministry of education is in charge of education policy and overall central funding. The Finnish national board of education, as the operational arm of the Ministry of education, is responsible for overall education provision and educational development, including the curriculum. Budgetary autonomy is established; budget is controlled by the local governments with input from principals. Personnel management is established. Teacher salaries are relatively fixed by civil service rules and municipalities choose their teachers under very stringent criteria. Participation of school councils in school governance is advanced. Parents trust school decisions because the system works very well. School and student assessment is advanced. Standardized student assessment is sample-based but schools evaluate their students continually. School autonomy and accountability are key components to ensure education quality. The transfer of core managerial responsibilities to schools promotes local accountability, helps reflect local priorities, values, and needs, and gives teachers the opportunity to establish a personal commitment to students and their parents. There are five indicators of school autonomy and accountability that can help benchmark an education system's policies that enable school autonomy and accountability: school autonomy in budget planning and approval; school autonomy in personnel management; the participation of the school council in school finance; the assessment of school and student performance; and school accountability to stakeholders. This report focuses specifically on policies in the area of school autonomy and accountability.